A note on edge-disjoint contractible Hamiltonian cycles in polyhedral maps - Ashish K Upadhyay; Dipendu Maity (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2014)
We present a necessary and sufficient condition for existence of edge-disjoint contractible Hamiltonian Cycles in the edge graph of polyhedral maps.